A meta-analysis of maturation-related variation in adolescent boy athletes' adaptations to short-term resistance training. Issue 11 (3rd June 2017) - Moran, Jason; Sandercock, Gavin R. H.; Ramírez-Campillo, Rodrigo; Meylan, César; Collison, Jay; Parry, Dave A.
ABSTRACT: This meta-analysis investigated the maturation-related pattern of adaptations to resistance training in boy athletes. We included studies examining the effects of 4–16-week resistance training programmes in healthy boy athletes aged 10–18 years. Pooled estimates of effect size for change in strength across all studies ( n  = 19) were calculated using the inverse–variance random effects model for meta-analyses. Estimates were also calculated for groups based on likely biological maturity status ("before", "during" and "after" peak height velocity). Using the standardised mean difference, resistance training increased strength across all groups (effect size = 0.98, [CI: 0.70–1.27]). Strength gains were larger during (1.11 [0.67–1.54]) and after (1.01 [0.56–1.46]) peak height velocity than before (0.5 [−0.06–1.07]). Adaptations to resistance training are greater in adolescent boys during or after peak height velocity. These findings should help coaches to optimise the timing of training programmes that are designed to improve strength in boy athletes.